An association of capital injection, restructuring, and financial performance of a company: a case study of Zimasco - Makuwatsine, Megi (Midlands State University, 2017)
Purpose: The purpose of this study is to examine the association of capital injection, restructuring and financial performance of a company, To investigate the reasons why capital injection and restructuring are failing to translate to desired performance levels and provide guidelines to protect the integrity of the association in a bid to guard against retarded financial performance. Design/methodology: The research made use of primary and secondary data at the disposal of the researcher. Primary data was collected through the use of questionnaires and interviews on the other side secondary data was gathered from textbooks, academic journals and other informative websites such as the business digest and newspapers. Quantitative research method was used to analyse the data. Findings:The research unveiled lack of adequate planning on restructuring, conflict of interest on priorities, lack of adequate support structures ,poor administration and general loss of business confidence as the major barriers to the success of the association. Research implications:The research was concluded by recommendations meant to protect the association from failure which makes the research a resounding success